2012
DOI: 10.3727/096504013x13775486749335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Proliferation and Invasion by MicroRNA-590-5p via Targeting PBRM1 in Clear Cell Renal Carcinoma Cells

Abstract: MicroRNAs (miRNAs) play an important role in cancer development. In our study, miR-590-5p is found to be upregulated in the examined renal cell carcinoma (RCC) cell lines. PBRM1 acts as tumor suppressor in RCC, and its downregulation is associated with increased proliferation and aggressive behavior in RCC. We confirmed that PBRM1 was a direct target of miR-590-5p. miR-590-5p could regulate PBRM1 mRNA and protein expressions in clear cell renal carcinoma (ccRCC) ACHN and 786-O cells. Downregulation of miR-590-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 30 publications
3
47
0
1
Order By: Relevance
“…It has been found that miRNAs are able to participate in the regulation of cell proliferation, differentiation, metabolism and apoptosis (5,6). A large number of studies have subsequently confirmed that miRNAs are involved in the pathogenesis of a number of human diseases, including cancer (7) and diseases involving the nervous system (8). In addition, researchers have also found that miRNAs are able to regulate tumor formation, infiltration and metastasis by directly binding to the mRNA of target gene (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that miRNAs are able to participate in the regulation of cell proliferation, differentiation, metabolism and apoptosis (5,6). A large number of studies have subsequently confirmed that miRNAs are involved in the pathogenesis of a number of human diseases, including cancer (7) and diseases involving the nervous system (8). In addition, researchers have also found that miRNAs are able to regulate tumor formation, infiltration and metastasis by directly binding to the mRNA of target gene (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…They control the expression of target genes by binding to the 3'-untranslated region (UTR) of their associated mRNAs and serve an important role in a variety of biological processes, including cell proliferation, apoptosis, differentiation, invasion and migration (5)(6)(7)(8). Accumulating studies are demonstrating that miRNAs are dysregulated in a variety of cancers and serve a critical role in tumorigenesis (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miR-590 is associated with the development of various types of cancer, including breast cancer (14), cervical cancer (15), clear cell renal carcinoma (16) and hepatocellular carcinoma (17). To the best of our knowledge, the present study is the first to investigate the expression and function of miR-590 in human gliomas.…”
Section: Introductionmentioning
confidence: 99%